Population size and nest site selection of the Spanish sparrow "Passer hispaniolensis" in the region of the River Krka (Croatia) - Mužinić, Jasmina; Purger, Dragica; Purger, Jenő J. (Zielona Góra: University of Zielona Góra, Faculty of Biological Sciences)
The breeding range of the Spanish sparrow, "Passer hispaniolensis", in Croatia is rapidly expanding. We studied the size of the nesting population and selection of nest site in an area partially included in the Krka National Park. Our results confirm that between 2004 and 2007 in the wider area of the Krka National Park the Spanish sparrow had occupied new localities, and that the number of 160 pairs recorded in 2003 had more than doubled (300?350) by 2007.
Keywords: Passer hispaniolensis; Spanish sparrow; invasive species; disperal; range; Skradin; Krka National Park